3D nanofluid flow over exponentially expanding surface of Oldroyd-B fluid - Aamir Ali (Elsevier, 2021)
Fluid motion is caused by the surface stretching, the temperature difference or the concentration difference etc. In this study, we will focus exclusively on the 3D nanofluid flow due to expanding surface of Oldroyd-B fluid which is extended in two directions. The flow over expanding surface has several applications in engineering and industrial processes for instance plastic sheet extrusion, hot rolling, paper processing, wire drawing, plastic films painting, and fiber glass etc. In current investigation, we have discussed the nanofluid flow over an expanding surface for Oldroyd-B fluid. It is possible to use nanofluids to enhance the fluid’s thermal conductivity. The equations that governs the flow are converted into nonlinear coupled ODE’s. The problem’s series solution was found using the method of homotopy analysis. Effects of Deborah number, thermophoretic and Brownian diffusion parameters, Prandtl and Schmidt numbers on the flow field are explored and discussed graphically. The relaxation/retardation times are noted to have contrasting effects on fluid velocity. Further, the diffusion parameter of nanoparticles enhance the temperature and nanofluid concentration.